Competitiveness of the MIPYMES engaged in the production and marketing of dairy products, 2014 (Revista Científica Estelí, 2015)
This research analyzes the competitiveness between the MIPYMES of dairy products, located in the city of Estelí in 2014, to suggest strategies to improve the competitiveness of these enterprises. The hypothesis as independent variable is the commercialization and the dependent variable is the competitiveness. This research is applied and quantitative; the study universe is 12 MIPYMES of dairy products and 110 distributors of these microenterprises. The sampling is Simple random probability. Surveys and semi -structured interviews were applied to business owners and their agents. This research requires three theoretical pillars: Competitiveness, commercialization and factors influencing in the competitiveness.Keywords: Competitiveness, Commercialization, MIPYMES, Estelí.